The effect of immediate feedback on mathematics learning achievement - Hadijah Hadijah; Isnarto Isnarto; Walid Walid (Jurnal Pijar Mipa, 2022)
Real facts at school show that the ability to solve problems is still considered low. Most students still make many mistakes in solving math problems. These mistakes must be directed to the right path to minimize repeated mistakes. Immediate feedback can be a solution to correct these errors. The purpose of this study was to examine the immediate feedback by the teacher during learning and their relationship to student learning achievement. The participants in this study consisted of 30 students from seventh grade. Data were collected from the final score on the number of subjects. Data were analyzed using descriptive statistics and paired sample t-tests to describe before dan after giving immediate feedback. Paired sample t-test analysis was also used to describe the relationship between immediate feedback on learning achievement. This study revealed a significant difference between immediate feedback and learning achievement. The final mean value shows the pretest average is higher than the posttest average. There is a positive relationship between immediate feedback and mathematics learning achievement. These findings can be used as a teacher's attention in providing feedback immediately during learning.